Convergence between Kazakhstans's financial systemand international standards: Overcoming difficulties - Natalya Uvarova (DANUBE: Law, Economics and Social Issues Review, 2015)
This article deals with the convergence of the Kazakh financial system with international standards in light of the new, enhanced agreement with the European Union on partnership and cooperation (January 19, 2015). Based on this research, the approaches used by the Kazakh financial system to converge with the European Union (EU) and the mechanism of implementing international standards in the national regulatory framework are determined. In practice, the study provides justification for the necessity of arranging the systematization of existing rules and regulations covering financial activity in the Republic, eliminating discrepancies between the national regulatory framework and international standards, and determining clear security guarantees for foreign investors' financial activity in the Republic. The research results are primarily focused on the development of public finance management theory. Theories and conclusions present in the study can be used in the educational processes of economic and legal institutions and in the policymaking activity of public finance management bodies.
Keywords: 330; Finance; International Standards; Public Management; Global Financial System; Financial Standards; Regulation